Novel Europium-Grafted 3D Covalent Organic Framework for Selective and Sensitive Fluorescence-Enhanced Detection of Levofloxacin - Junyi Zhao; Chao Zhang; Zhijie Qiu; Zerong Zhang; Xiaorou Lin; Shibin Huang; Jianfeng Zhang; Jingpeng Wu; Li Liao; Rui Wang (Sensors)
Levofloxacin (LVFX), a fluoroquinolone antibacterial agent widely used in treating bacterial infections, poses significant risks when overused, necessitating the development of reliable and efficient detection methods. Herein, we introduce Eu@SUZ−103, a novel europium-grafted three-dimensional covalent organic framework (COF) featuring an eight-connected bcu net, for the selective detection of LVFX in serum and urine. Its 3D architecture facilitates rapid LVFX diffusion to luminescent sites, producing notably enhanced fluorescence and high sensitivity. Evaluations in complex biological matrices revealed excellent performance encompassing a broad linear range (5–2000 μM) and a low detection limit. Altogether, Eu@SUZ−103 extends the practical scope of 3D COFs in fluorescence-based sensing, offering a robust platform for accurate, efficient, and selective LVFX monitoring in clinical and environmental applications.